1997
DOI: 10.1007/bf03403912
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Fluoridation on the Bone Mineral Density of Young Women

Abstract: Permission to Use Statement In presenting this thesis in partial fulfilment of the requirements for a Postgraduate degree from the University of Saskatchewan, I agree that the Libraries of the University may make it freely available for inspection. I further agree that permission for copying of this thesis in any manner, in whole or in part, for scholarly purposes may be granted by the professor or professors who supervised my thesis work, or, in their absence, by the Head of the Department or the Dean of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…For the LS, Slemenda et al (25) report a bone mineral accumulation of 30% of adult BMC over 3 peripubertal years as determined by Tanner staging. In the present study, using a value of 60 g as an average spinal BMC for a young adult female, (33) 32% of adult BMC was accrued in the 2 years around PBMCV. The clinical significance of these percentages can be appreciated by considering the fact that as much bone mineral is being laid down during the adolescent years as most people will lose during their entire adult lives (12) …”
Section: Discussionmentioning
confidence: 71%
“…For the LS, Slemenda et al (25) report a bone mineral accumulation of 30% of adult BMC over 3 peripubertal years as determined by Tanner staging. In the present study, using a value of 60 g as an average spinal BMC for a young adult female, (33) 32% of adult BMC was accrued in the 2 years around PBMCV. The clinical significance of these percentages can be appreciated by considering the fact that as much bone mineral is being laid down during the adolescent years as most people will lose during their entire adult lives (12) …”
Section: Discussionmentioning
confidence: 71%
“…The 76 mothers (mean age, 40 years) had a BMC of 2164 g and the 37 fathers (mean age, 45 years) had a BMC of 2884 g. A separate unpublished study of 59 men (mean age, 40 years) and 32 women (mean age, 36 years) revealed BMC values of 2880 g and 2181 g, respectively. Finally, a study of 57 younger women (22) (mean age, 21 years) revealed a BMC of 2180 g. Averaging these adult values and converting to calcium equivalents gives a mean young adult skeletal calcium of 928 g for men and 700 g for women. If we take these to be estimates of the young adult calcium values of the boys and girls in this study, approximately 26% of adult calcium is gained in the 2 years of peak skeletal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a study of 57 younger women (22) (mean age, 21 years) revealed a BMC of 2180 g. Averaging these adult values and converting to calcium equivalents gives a mean young adult skeletal calcium of 928 g for men and 700 g for women. If we take these to be estimates of the young adult calcium values of the boys and girls in this study, approximately 26% of adult calcium is gained in the 2 years of peak skeletal growth.…”
mentioning
confidence: 99%
“…Another study compared “unexplained” bone fracture rates among 6- to 12-year-old Mexican children living in areas with water fluoride concentrations ranging from 0 to >12 ppm, and found that the fracture rates were similar across locations (10). A more refined study of young (18- 25-year-old) Canadian women compared lumbar spine and femoral bone density of those who had lived in a low water-fluoride (0.1 ppm) community to those who had lived in an optimally fluoridated (1.0 ppm) community (11). This study controlled for height, weight, physical activity and dietary factors, and it assessed bone density using dual-energy x-ray absorptiometry (DXA).…”
Section: Introductionmentioning
confidence: 99%